Accurate Range for Variable Fractional-Delay Filtering - Tian-Bo Deng (2005 5th International Conference on Information Communications and Signal Processing, 2006)
To perform variable fractional-delay (VFD) filtering, the VFD parameter p is assumed to take fractional numbers in pisin[0,1] and pisin[-0.5, 0.5] in the literature, but it needs to be clarified that which range should be adopted for achieving high-accuracy VFD filtering. In this paper, we first analyze the accurate range qualitatively, and then utilize interpolation examples to demonstrate that range pisin [-0.5, 0.5] is the better choice for accurate VFD filtering